The reflection of the pro-climate attitudes of Nordic consumers in their carbon footprints - Tolkyn Abdirova 1991- (2022)
Due to their production and supply of green energy, the Nordic countries are frequently seen as sustainable. However, the nations rank among the highest in the world in terms of their consumption-based carbon footprints (CBCFs). The aim of the thesis is to learn how pro-climate attitudes (PCA) and consumption habits vary among the Nordic countries and how this is reflected in their carbon footprint. The study utilizes the data of around 8000 respondents, collected with the help of an online survey that was published in the Nordic countries. The thesis analyzes how PCA and several sociodemographic variables are associated with CBCFs regarding diet, transport, housing, leisure travel, goods and services, pets, and summer cottages. Using GNU PSPP, bivariate and regression analyses were carried out. Bivariate analysis revealed that Denmark (8.6 tCO2-eq) had the highest personal CBCF, followed by Iceland (8 tCO2-eq), Finland (7.9 tCO2-eq), Norway (7.1 tCO2-eq), and Sweden (6.5 tCO2-eq). The Nordic CBCF has been most significantly impacted by dietary habits (average 1.9 tCO2-eq), followed by goods and services (average 1.8 tCO2-eq), and transportation (average 1.4 tCO2-eq). Aside from Norway, the regression analysis's findings showed that CBCFs declined as PCA levels rose. Income was the sociodemographic variable that affected CBCFs most significantly. In general, the higher the income, the bigger the footprint. The analysis supported the need for demand-side policies in the Nordic nations since high standards of living result in high carbon footprints per person even in decarbonized energy supply systems.